Variations in the magnetic declination at mid-latitude European stations during the Carrington-like event on 29 October 2003 - F. Valach; M. Váczyová; E. Koči; E. Koči (Annales Geophysicae)
Based on the declination observed at mid-latitude European stations (geomagnetic latitudes 34–58° N), we studied the current system that is a candidate for the cause of the sharp drop in horizontal intensity (H) of the geomagnetic field that occurred in that part of the globe at ∼ 09:00 MLT (magnetic local time) on 29 October 2003. The newest knowledge says that the current system consisted of a pair of field-aligned currents (FACs) forming a dayside current wedge: in the early afternoon sector, it was a stationary upward FAC, and in the dawn sector, it was a westward-moving downward FAC. Simultaneously with the drop in H, the current wedge caused a sine-like profile in declination observed at the mid-latitude European stations. By studying this profile at individual observatories, we found a velocity of −1.08° min−1 ± 0.38° min−1 for the wedge centre, roughly half the velocity of the westward-moving downward FAC. Our results contribute to arguments that the dayside current wedge was the probable cause of the H drop on 29 October 2003.